Seminar Digital Marketing Terhadap Produk UMKM untuk Meningkatkan Kesejahteraan Masyarakat Desa Randuwatang - Muhammad Farid Nasrulloh; Faisol Hidayatulloh; Wisnu Mahendri; Khotim Fadhli; Putri Marsella Zalianti; Mohammad Jafar Sodiq Maksum (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2024)
Currently, not many MSMEs are using this sophisticated digital platform, due to a lack of understanding about digital marketing which can boost people's economies. Based on the results of a pre-survey with several UMKM players, especially the food sector, that they do not yet have halal product certification, because: (1) They do not understand the importance of digital marketing and its impact on UMKM to improve the welfare of the Randuwatang community. (2) UMKM players do not yet know how to apply online platforms to produce interesting content to attract the target market. (3) UMKM players are still seasonal in opening businesses because other sources of livelihood are more dominant, such as drivers, craftsmen, etc., than UMKM. Based on the problems faced by partners, community service activities in the LPPM scheme are carried out through digital marketing seminars on UMKM products to improve the welfare of the Randuwatang village community. The method used in this digital marketing seminar is providing material regarding the importance of digital marketing for UMKM in the current millennial era. The method used is an interactive discussion in the form of questions and answers by participants who do not understand and answered directly by the resource person. From the implementation of socialization activities, it was concluded that digital marketing had proven to be an effective tool for improving the welfare of the community in Randuwatang Village.